2019
DOI: 10.9755/ejfa.2019.v31.i7.1972
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of essential oils on mycelial growth of Fusarium oxysporum and Bortytis cinerea

Abstract: In vitro study of the effect of different volumes of twelve essential oils on the mycelial growth of economically significant phytopathogenic fungi (Fusarium oxysporum and Botrytis cinerea) and it was compared to the effect of a fungicide. The antifungal activity of essential oils is decreased with the duration of incubation and it differs depending on the type of phytopathogenic fungus and the applied volume. The most effective antifungal effect on both tested fungi was in the essential oil of thyme, with low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 0 publications
7
15
0
Order By: Relevance
“…Our research data confirmed that the chemical composition of tested EO is in line with what is already have been described in the literature [ 16 , 17 , 19 , 20 , 26 , 29 , 30 , 31 , 32 , 33 , 34 ]. Oliveira et al [ 16 ] reported that thymol and p -cymene were abundant components in identified 28 compounds of thyme EO.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our research data confirmed that the chemical composition of tested EO is in line with what is already have been described in the literature [ 16 , 17 , 19 , 20 , 26 , 29 , 30 , 31 , 32 , 33 , 34 ]. Oliveira et al [ 16 ] reported that thymol and p -cymene were abundant components in identified 28 compounds of thyme EO.…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that the antifungal effect presence of the dominant components of EO, as main activity carriers. Palfi et al [ 17 ] reported that thyme, sage, and peppermint EO totally inhibited the mycelial growth of F. oxysporum in vitro; however, sage EO had a low inhibitory effect against B. cinerea . Oliveira et al [ 32 ] observed that 5 μL/mL peppermint EO showed 100% MGI on all tested Colletotrichum stains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the majority of the papers about antifungal and antibacterial effects of EOs [ 17 , 18 ], a dose dependent response was observed for almost all of the EOs tested in this study, the effects being stronger at 1000 ppm than at 500 ppm.…”
Section: Discussionsupporting
confidence: 88%
“…The most effective antifungal effect on both Fusarium oxysporum and Botrytis cinerea was in the essential oil of thyme. [9]. Alternaria solani can infect every part of the plant (causing foliage blight, fruit lesions and stem collar rot) and can damage during all stages of plant development [10].…”
Section: Introductionmentioning
confidence: 99%